Exploring Rumelhart’s model for academic reading among undergraduates / Nurul Bazilah Abd. Hamid, Doreen Dillah and Sathiyaperba Subramaniam - Abd. Hamid, Nurul Bazilah; Dillah, Doreen; Subramaniam, Sathiyaperba (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Reading strategies are deemed important in academic reading among English as a second language (ESL) students because these strategies can help them to grasp a better understanding of academic texts. By incorporating the top-down and bottom-up strategies via Rumelhart’s Interactive Theory, this study explored undergraduates’ use of strategies for academic reading. For this purpose, 207 undergraduates were selected using purposive sampling method, while the quantitative research approach was utilised to gauge the necessary data. In specific, a 5-Likert scale questionnaire survey comprising 48 items distributed across 5 sections was administered among the participants. Results indicated that the top-down and bottom-up strategies are significantly correlated in the aspect of academic reading. Important findings from the study are crucial to guide instructors in creating language and classroom interventions with the focus on incorporating effective reading skills that are specifically tailored for better comprehension of academic texts among L2 learners.